«Orteke» tradition in cultures of turkic-speaking nationalities - Aбишевa Б. (Journal of Oriental Studies, 2017)
The article discusses the genesis of the genre Orteke, the history of its origin and features of functioning. Orteke origins date back to ancient times and are associated with early nomadic and hunting way of life of the Central Asian nations. In this genre are presented elements of several kinds of art: folk and the actual musical instrument, dance, and gaming, theater and arts and crafts. Orteke associated with the most important constants worldview culture, the so-called “ideological syncretism”, not only Turks, but also in the whole of the nomadic peoples of Central Asia.